2003
DOI: 10.1021/cm021333t
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Layer Deposition of Platinum Thin Films

Abstract: Platinum thin films were grown at 300 °C by atomic layer deposition (ALD) using (methylcyclopentadienyl)trimethylplatinum (MeCpPtMe3) and oxygen as precursors. The films had excellent uniformity, low resistivity, and low-impurity contents. Structural studies by X-ray diffraction showed that the films were strongly (111) oriented. Growth rates of 0.45 Å cycle-1 were obtained with 4 s total cycle times. The film thickness was found to linearly depend on the number of the reaction cycles. Also, the possible react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

30
419
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 385 publications
(454 citation statements)
references
References 26 publications
30
419
2
Order By: Relevance
“…Both processes resulted in smooth films and had generally lower root-mean-square roughness values ͑0.4-0.7 nm͒ than reported ͑0.75-4 nm͒. [1][2][3] Because island growth is known to promote surface roughening, 19 the fast nucleation and, consequently, more pronounced layer-by-layer growth can be related to the lower surface roughness obtained for the remote plasma ALD process.…”
Section: Resultsmentioning
confidence: 83%
See 4 more Smart Citations
“…Both processes resulted in smooth films and had generally lower root-mean-square roughness values ͑0.4-0.7 nm͒ than reported ͑0.75-4 nm͒. [1][2][3] Because island growth is known to promote surface roughening, 19 the fast nucleation and, consequently, more pronounced layer-by-layer growth can be related to the lower surface roughness obtained for the remote plasma ALD process.…”
Section: Resultsmentioning
confidence: 83%
“…Pt growth on these substrates could only be achieved by using a higher O 2 pressure ͑Ͼ0.8 mbar͒ as also typically used in the literature. 1,3 On the contrary, remote plasma ALD of Pt ͑0.5 s O 2 plasma͒ leads to immediate growth without a substantial nucleation delay. From the ellipsometry measurements, which have a reduced accuracy in the first 1-2 nm, it is concluded that growth per cycle is constant after the first 50 cycles.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations